Utilisation of maternal health services: a mixed-methods study of women attending antenatal care at primary health care centres in Abuja, Nigeria - Azuka Chinweokwu Ezeike; Duro Clement Dolapo; Elkenah Chubike Ndie (BMC Primary Care, 2026)
Abstract Background Due to restricted access to health care, maternal mortality rates in low-income countries are unacceptably high. Adequate health-care utilisation has been identified as crucial in the drive to improve maternal health indices. Objective This study aimed to determine the level of utilisation of maternal health services among women attending Antenatal care at Primary Health Care Centres (PHCs) in Abuja, Federal Capital Territory. Methods This study employed a mixed-methods design using the convergent parallel approach. The quantitative arm employed a cross-sectional design with data collected using a semi-structured five-section questionnaire, whereas the qualitative arm consisted of focus group discussions (FGD). The study was conducted over a four-month period, from September 2022 to January 2023. Participants were selected from women receiving antenatal care at 12 primary health care centres in Abuja, using multistage sampling. Quantitative data were analysed using SPSS version 25, while qualitative data were analysed thematically. A p-value of less than 0.05 at the 95% confidence level was considered statistically significant. Results Of the 370 respondents, 365 had complete entries and were included in the final analysis. In the current pregnancy, up to 82.7% of women booked antenatal care in the second trimester. Antenatal care, facility-based delivery, and postnatal care coverage were 95.6%, 80%, and 28.2%, respectively, in their most recent pregnancy. Maternal educational level and employment status were found to be significantly associated with maternal health service utilisation ( p < 0.05). Findings from the FGDs showed that quality of care and the availability of caring health workers influenced participants’ choice of health facility. Participants recommended increasing the number of health facilities and ensuring an adequate health workforce. Conclusion This study showed encouraging antenatal care attendance and facility-based deliveries. However, postnatal care attendance remained very low, reflecting poor health literacy. Maternal education and employment, increasing healthcare staffing, and reducing the cost of care could help address these gaps. Periodic evaluation of the needs of primary health care end users, followed by programme restructuring to address those needs, is essential.